A balanced faith, a balanced life another key to happiness - Locker, Markus Ekkehard; Goebel, Udo (2016)
The starting point of this is that a balanced faith life is the foundation to happiness in the Christian sense. This article considers this suggestion from a historical perspective, i.e., by a survey of three reformations that occurred within the last five hundred years. Specifically, these are Luther's challenge to orthodoxy, the Pietist movement in the seventeenth, and the Social Gospel and Missionary Movement in the nineteenth and twentieth centuries. The article specifies what each of these reformations contributed to the development of an understanding of faith as a balance of notitia, assensus, and fiducia. To shed light on these dimensions, the article will look at three key concepts that characterize these reformations; orthodoxy, orthopathy and orthopraxy. Biblical references will be used to illustrate each point.
Keywords: Religious orthodoxy; Happiness